1991
DOI: 10.1164/ajrccm/143.5_pt_1.1025
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Leukotriene E4Concentrations Increase after Aspirin Challenge in Aspirin-sensitive Asthmatic Subjects

Abstract: Urinary leukotriene E4 (LTE4) concentrations have been measured in six asthmatic patients with aspirin sensitivity and in five asthmatic subjects tolerant of aspirin, before and after provocation with aspirin or placebo. Aspirin-sensitive subjects showed an average 21% fall in FEV1 after aspirin challenge whereas control individuals had a 2% fall in FEV1 after ingestion of 100 mg aspirin. The resting urinary LTE4 concentrations in asthmatic subjects sensitive to aspirin were 243 pg/mg creatinine (range 50 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
261
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(297 citation statements)
references
References 10 publications
30
261
0
2
Order By: Relevance
“…In addition, urinary excretion of LTE 4 and of cotinine, the major urinary metabolite of nicotine, were also closely related. The correlation between the number of cigarettes smoked per day and the urinary excretion of LTE 4 reveals that smoking of 22 cigarettes per day results in a urinary excretion of LTE 4 that is similar to the baseline excretion of patients with asthma [15], whereas healthy volunteers [15] excreted similar amounts of LTE 4, as reported in the present study. Furthermore, smoking of more than 35 cigarettes per day enhances LTE 4 excretion to a rate that is similar to the LTE 4 excretion of asthmatics after allergen exposure.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, urinary excretion of LTE 4 and of cotinine, the major urinary metabolite of nicotine, were also closely related. The correlation between the number of cigarettes smoked per day and the urinary excretion of LTE 4 reveals that smoking of 22 cigarettes per day results in a urinary excretion of LTE 4 that is similar to the baseline excretion of patients with asthma [15], whereas healthy volunteers [15] excreted similar amounts of LTE 4, as reported in the present study. Furthermore, smoking of more than 35 cigarettes per day enhances LTE 4 excretion to a rate that is similar to the LTE 4 excretion of asthmatics after allergen exposure.…”
Section: Discussionsupporting
confidence: 85%
“…In contrast, the urinary levels of LTE 4 remained unchanged during the course of bronchoprovocation in five asthmatics who did not develop an airway obstruction to inhaled lysineaspirin [192]. This observation was in line with concurrent reports that oral aspirin challenge increased urinary LTE 4 [214,215].…”
Section: Aspirin-induced Bronchoconstrictionsupporting
confidence: 87%
“…It has consistently been observed that the baseline urinary excretion of LTE 4 is significantly higher in aspirin-intolerant asthmatics than in aspirin-tolerant asthmatics [192,214,215]. In addition, it was recently observed that there was a marked overexpression of the LTC 4 synthase in bronchial biopsies of aspirin-intolerant asthmatics [50].…”
Section: Antileukotrienes In Aspirin-intolerant Asthmamentioning
confidence: 99%
“…cysteinyl leukotrienes | mast cells | mucosal immunology | lung | epithelial cell C ysteinyl leukotrienes (cysLTs), leukotriene C 4 (LTC 4 ), LTD 4 , and LTE 4 are lipid mediators detected during asthma exacerbations triggered by allergen (1), aspirin (2,3), and respiratory viruses (4). The cysLTs elicit vascular permeability, inflammation, and bronchoconstriction through three G-protein-coupled receptors.…”
mentioning
confidence: 99%